2022
DOI: 10.1017/s0033291722000976
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and substance abuse increase the COVID-19 mortality risk

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has been a global challenge. High mortality rates have been reported in some risk groups, including patients with pre-existing mental disorders. Methods We used electronic health records to retrospectively identify people infected due to COVID-19 (between March 2020 and March 2021) in the three territories of the Basque Country. COVID-19 cases were defined as individuals who had tested positive on a reverse transcription-polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…These studies together with ours, point in another direction than the many studies nding a higher prevalence of SARS-CoV-2, more severe morbidity and greater mortality related to the disease among PWUD (12)(13)(14)(15). Strathdee and colleagues found a prevalence of SARS-CoV-2 among PWUD in the San Diego-Tijuana border to be higher than estimates from the general population in either city (32,33).…”
Section: Discussionsupporting
confidence: 57%
“…These studies together with ours, point in another direction than the many studies nding a higher prevalence of SARS-CoV-2, more severe morbidity and greater mortality related to the disease among PWUD (12)(13)(14)(15). Strathdee and colleagues found a prevalence of SARS-CoV-2 among PWUD in the San Diego-Tijuana border to be higher than estimates from the general population in either city (32,33).…”
Section: Discussionsupporting
confidence: 57%
“…Regarding anxiety disorders and COVID-19 death, our findings are in line with published sources ( Poblador-Plou et al, 2020 ; Catalan et al, 2022 ). However, the strong association between anxiety disorders and mechanical ventilation in our study is a novel finding.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, COVID-19 patients with comorbid anxiety disorders were found to have a 2.4 times greater risk of mortality than those without anxiety disorders ( Teixeira et al, 2020 ). In a recent study, Catalan et al analyzed data on 157,246 people from the Basque Country (Spain) and observed that anxiety disorders [OR: 1.54] were associated with an increased risk of hospital admission, but were not associated with a higher mortality risk among admitted patients ( Catalan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of our meta-analysis, the Center for Disease Control and Prevention (CDC) updated its list of conditions associated with severe COVID-19, including schizophrenia. The increased COVID-19 mortality in schizophrenia-spectrum disorders was confirmed in other countries [17–19] and synthetized in a meta-analysis published in 2022 confirming that schizophrenia was a risk factor for both contracting COVID-19 infection and developing a severe/lethal form of the infection [20 ▪▪ ]. In this meta-analysis, 263 207 patients from 10 studies were included and the relative risk ratio of increased mortality was 2.2 (1.54–3.20).…”
Section: Increased Risk Of Infection and Increased Mortalitymentioning
confidence: 54%